Bloodletting in Babylonia Revisited - Geller, M. J. (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2022)
The question of bloodletting in Babylonia (and surgery in general) has hardly been studied, since evidence is sparse, while at the same time bloodletting in the Babylonian Talmud has been assumed to have been employed, although based upon questionable medieval interpretations of vague and doubtful terminology. However, when descriptions from cuneiform medicine are combined with evidence from Aramaic sources, a somewhat clearer picture emerges of a possible limited use of a bloodletting procedure in Babylonia, in both earlier and later periods.